Kändisförfattarens varumärke i Finland - Hypén, Tarja-Lisa (K&K - Kultur og Klasse, 2012)
THE BRAND OF THE CELEBRITY AUTHOR IN FINLAND | In the 21st century, the celebrity author has begun to interest researchers not only as a marketing phenomenon, but also as the literary institution’s own phenomenon. In my article, I explore the relationship of the celebrity author to the so-called acclaimed authors of modern times. In Anglo-American research, the celebrity author and the bestselling author are distinguished as separate author types, but in the case of Finnish Jari Tervo, these types combine. For almost 20 years, Jari Tervo has been among both the most sold and the most visible celebrity authors in his home country. I examine how the publicity and brand of the Finnish celebrity author are formed. I consider how the brand affects the author’s works on the one hand, and the reception of the works on the other. I point out the limiting effects of the brand, but I also examine how, in combining the high and the low, it affords mobility in the literary fields while it also offers an opportunity to influence society.